THE ROLE OF GREEN PRODUCT QUALITY AND AESTHETIC CAPABILITIES IN ENVIRONMENTAL PERFORMANCE - DR. Momtej Abida; Dr. Khalid Jameel Kami; Saadulldeen Ali Hussein; Krar Mohsin Thajil (Journal Park Publishing, 2023)
Given that the goal of green product quality is to produce environmentally friendly products while considering environmental issues, the impact of green product quality on environmental performance provides a highly useful means to achieve these objectives and mitigate environmental problems. Therefore, this study aims to examine the interactive role played by aesthetic capabilities (the organizational mirror) in the relationship between green product quality and environmental performance in the South Refineries Company, addressing the problem of environmental pollution caused by petroleum products. To achieve this objective, a questionnaire will be developed to ensure the presence of a relationship among the variables of the study. The data will be collected using the questionnaire as the primary data collection tool, designed based on validated foreign scales that have been scientifically tested.
Keywords: aesthetic abilities, organizational women, green products, green product quality, environmental performance.